Manikins for textile evaluation - Nayak, Rajkishore; Padhye, Rajiv (Textile Institute book series., 2017)
Manikins for Textile Evaluation is a key resource for all those engaged in textile and apparel development and production, and for academics engaged in research into textile science and technology. Creating garments that work with the human form, both stationary and in motion, is a complex task that requires extensive testing and evaluation. Manikins allow for performance testing of textiles in a safe, controlled, and appropriate environment, and are a key element in developing new textile products. Everyday apparel needs to be assessed for comfort, sizing and fit, and ergonomics, while technical and protective garments require extensive safety and performance testing. Manikins therefore range from simple representations of the human body to complex designs that simulate body temperature, sweating, and motion. Manikins are safe for use in hazardous testing environments, such as fire and flame protection, where wearer trials would be impossible. This book provides extensive coverage of manikin-based evaluation of protective, heat and flame resistant, medical, and automotive textile applications. The role of manikins in the development of day-to-day garments is also discussed, including fit, comfort, and ergonomics. The book is a key resource for all those engaged in textile and apparel development and production, and for academics engaged in research into textile science and technology.